2017
DOI: 10.1038/s41598-017-12136-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of lncRNAs and mRNAs in skeletal muscle of rainbow trout (Oncorhynchus mykiss) exposed to estradiol

Abstract: Estradiol (E2) is a steroid hormone that negatively affects muscle growth in rainbow trout (Oncorhynchus mykiss), but the mechanisms directing with this response are not fully understood. To better characterize the effects of E2 in muscle, we identified differentially regulated mRNAs and lncRNAs in juvenile rainbow trout exposed to E2. Here, we performed next-generation RNA sequencing and comprehensive bioinformatics analyses to characterize the transcriptome profiles, including mRNAs and long noncoding RNAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…In this context, rapid glucocorticoid effects on the regulation of focal adhesion in mammalian skeletal muscle has been previously reported (6). In addition, protocols of exogenous administration of another steroid-family hormone (estradiol) in rainbow trout reveal the strong regulation of several genes involved in focal adhesion processes in the skeletal muscle (43). To date, diverse focal adhesion-related genes have been identified as glucocorticoidresponsive genes, suggesting a critical role of this process in the adaptive stress response in mammals (21,24).…”
Section: Discussionmentioning
confidence: 89%
“…In this context, rapid glucocorticoid effects on the regulation of focal adhesion in mammalian skeletal muscle has been previously reported (6). In addition, protocols of exogenous administration of another steroid-family hormone (estradiol) in rainbow trout reveal the strong regulation of several genes involved in focal adhesion processes in the skeletal muscle (43). To date, diverse focal adhesion-related genes have been identified as glucocorticoidresponsive genes, suggesting a critical role of this process in the adaptive stress response in mammals (21,24).…”
Section: Discussionmentioning
confidence: 89%
“…RNA-seq is an effective method to identify novel genes and their potential functional properties. Recent studies have confirmed the contribution of transcriptome analysis at the molecular level [ 18 , 19 , 25 ]. The current results indicated the accuracy and high quality of sequencing data, which were then used for subsequent research.…”
Section: Discussionmentioning
confidence: 92%
“…Increased expression of genes involved in ubiquitin conjugating enzyme complex was observed in our previous study (WANG et al 2017). Our current findings and these observations together implicate DNA methylation as a major regulator of ubiquitin conjugating enzyme complex gene expression.…”
Section: Genes With Differentially Methylated Regionssupporting
confidence: 87%